Environmental control on the structure of echinoid assemblages in the Bellingshausen Sea (Antarctica) - Moya-Ruiz, Francisca; Saucède, Thomas; Manjón-Cabeza, María Eugenia (2012)
The Bellingshausen Sea is one of the most remote and least surveyed seas of the Southern Ocean, so that little was known about benthic communities and those factors that determine community structuring until recently. The present work aims at characterizing the structure and spatial distribution of echinoid assemblages in the Bellingshausen Sea, as well as identifying the environmental factors that determine assemblage structuring. Echinoids were collected at 32 stations using an Agassiz trawl, at depths of 86–3,304 m, during BENTART oceanographic expeditions led in 2003 and 2006. Sediment and bottom water properties were analysed using an USNEL-type box corer and a Neil Brown Instrument System Mark III CTD, respectively. Echinoids were found at all stations, except Peter I Island. Seventeen species were identified, representing 22 % of the echinoid species present in the Southern Ocean and increasing twofold the number of species recorded in the Bellingshausen Sea so far. The echinoid fauna is dominated by the very abundant species Sterechinus antarcticus. Depth is the key factor that determines the nature of echinoid assemblages, which are mainly divided into the continental shelf, the slope and the deep-sea basin. In addition, sediment properties, namely redox values, organic matter and mud content, best match species dispersion on the shelf. Sediment properties affect echinoid distribution depending on species food range and feeding strategy. As it might be expected, sediment properties more strongly influence specialist feeders (Schizasteridae and Cidaridae) than generalists (Echinidae). SI